Konstruksi Sosial-Budaya dalam Pembangunan Ruang Publik di Kota Makassar: Menatap Pantai Losari Dulu, Kini, dan Masa Mendatang - Ahmadin Ahmadin (Rayhan Intermedia, 2021)
Ethnic symbols are an important part of the social survival of a community living in a certain area. Apart from being a marker of socio-cultural identity, the symbol also becomes a certain ethnic pride. This paper examines the forms of social and cultural construction in the development of public spaces in Makassar City, which are associated with the existence and function of Losari beach in the past, present, and in the future. The appearance of Losari beach now or rather the Losari pavilion, seems to show a face which is a depiction of the four ethnic groups in South Sulawesi, namely Makassar, Bugis, Mandar, and Toraja. However, an interesting question related to this is is it true that the procurement of ethnic symbols in this public space is a form of cultural awareness? Or maybe just an economic strategy wrapped in ethnic identity? From these two questions, a description of the existence of Losari beach as a cross-age public space will be studied which is related to the theory of social construction. It will even go so far as to offer thought-provoking recommendations for the future of this historic beach.